2020
DOI: 10.1021/acs.orglett.0c00235
|View full text |Cite
|
Sign up to set email alerts
|

Access to Fluorenones Using Benzocyclopentynone Surrogate as Partner for the [2 + 2 + 2] Cycloaddition Reaction

Abstract: A convenient and versatile procedure for the straightforward synthesis of substituted fluorenones as valuable scaffolds is described under rhodium catalysis. The present [2 + 2 + 2] cycloaddition reaction of diynes with 3-acetoxy or-3alkoxyindenones as surrogates of the highly reactive benzocyclopentynone 2π partner allows the preparation of various fluorenonetype derivatives in good yields and provides an additional and tunable process for the generation of more challenging molecules with application in pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…[52] Commeiras . [53] The yield was also dependent on the reaction conditions, whereas decreasing temperature led to lower yields (at 50°C and room temperature yields were 29 % and 28 % respectively).…”
Section: Intermolecular Synthesis Of Fluorenonesmentioning
confidence: 96%
“…[52] Commeiras . [53] The yield was also dependent on the reaction conditions, whereas decreasing temperature led to lower yields (at 50°C and room temperature yields were 29 % and 28 % respectively).…”
Section: Intermolecular Synthesis Of Fluorenonesmentioning
confidence: 96%
“…In 2020, Amatore, Commeiras, and co-workers reported the Rh-catalyzed [2+2+2] cycloaddition reaction of 1,6diynes with 3-acetoxy or-3-alkoxyindenones as surrogates of the highly reactive benzocyclopentynone 2 partner, in the presence of 10 mol% [Rh(C 6 H 10 )Cl] 2 and racemic BINAP combined with AgBF 4 and CaH 2 as a hydride source additive at 80 °C in anhydrous 1,2-dichloroethane for 12 h to provide the desired substituted fluorenones in 36-81% yield (Scheme 29). 91 Optimization of the reaction indicated that cycloaddition carried out in the presence of AgSbF 6 or AgOTf led to side reactions. Variable yields were obtained with diynes bearing different tethers (up to 81% with a gem-dicyanomethylene tether).…”
Section: Scheme 28mentioning
confidence: 99%
“…Similarly, Amatore and co‐workers designed a straightforward methodology for the preparation of substituted fluorenones 81 from diynes 79 and 3‐alkoxy, 3‐acetoxyindenones 80 via [2+2+2] cycloaddition reaction using Rh‐catalyst (Scheme 29). [48] The formation of fluorenone through the oxidative coupling of 79 with Rh‐catalyst to give rhodacyclopentadiene intermediate. Then undergoes rearomatization after reductive elimination, which affords the corresponding fluorenone 81 .…”
Section: Reactions Of Alkyl Enol Ethersmentioning
confidence: 99%